EFKTIVITAS PENGOLAHAN BAHAN PUSTAKA PADA PERPUSTAKAAN FISIP UNIVERSITAS TANJUNGPURA - Narto, Siti Laila; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe finl project discusses theâ€Effectiveness of Library Materials Processing at the Library Fisip Universitas Tanjungpuraâ€ which discusses the measurement of a success rate in achieving the objectives, in the proccess of processing library materials there are visitors coming. And the purpose of this research is to find out how library managers manage books with various titles. And what are the constraints that are often faced by the library manager in the processing stage of existing library materials, what are the problems in the existing library materials in the Fisip library begins with searching the class number using the DDC manual, then inputting the book data, recording the data manually in the library master book, and paste lending notes, then placed on the bookshelf so that students can use as reference material.Â Keywords : Effectiveness, Processing, Library MaterialsÂ